Formation of competency of health protection at the sanitary and hygienic culture mastering by students of agroecological collges - Suk, Alina (ScienceRise: Pedagogical Education, 2017)
The attitude to health as to the value forms especially actively at the adolescent and young age and is a result of the influence of education and surrounding social environment. Especially, the importance of the problem of formation of the value attitude to health in students of an agroecological college is conditioned by their age features and mastering of the future profession. Pupils’ entrance to a college is a crucial moment of their socialization. This moment coincides in time with their age crisis of development, it brings serious test of their adaptive possibilities. A new collective, new regime, new character of interrelations needs from students new forms of the study and behavior. Adapting to new conditions, an organism mobilizes the system of adaptive reactions for this aim. During the study in an agroecological college a student must form such professional dynamic stereotype and lifestyle that favors keeping and strengthening of his/her health and others’ one. The results of the research determined the problems that need further elaboration: – the role of a collective of an educational institution in the sanitary-hygienic upbringing of students; – the activity and interaction of social institutions as to the formation of the competence of bases of health protection of the sanitary-hygienic culture of future specialists of the agroecological branch; – the substantiation of the professionally directed special course as to health protection in the system of training of future specialists of the agroecological branch